Effect of Land Use and Slope Position on Infiltration Characteristics on Sandstone-Derived Soils of Southern Nigeria - U. E, Utin (International Journal of Sustainable Agricultural Research, 2021)
A study of some soil properties that influence infiltration under different land use types and slope positions in sandstone-derived soils was carried out in Akwa Ibom State, Southern Nigeria. Soil samples were collected in triplicate for laboratory analyses and infiltration tests were conducted using the double ring infiltrometer method. Analysis of variance, correlation and regression analyses were used to assess the data Oil Palm Plantation and Fallow Land increased the organic matter content of the soil, reduced bulk density, increased the soil porosity and aggregate stability over Continuously Cultivated Land. Downslope soil movement caused the upper slopes to lose their clay and organic matter to the middle and lower slope soils. Initial infiltration rate, final infiltration rate, cumulative infiltration, sorptivity and transmissivity varied highly across the studied locations but were not significantly (P ≤ 0.05) affected by land use, slope position and their interactions. Apparently higher infiltration rates were observed in all slope positions under Oil Palm Plantation and Fallow Land as a result of their apparently higher clay contents, total porosity, mean weight diameter, saturated hydraulic conductivity and organic matter contents over those of Continuously Cultivated Land. Heavier organic matter input will help to modify the upper slope soils for increased infiltration rates. Plantation agriculture should be adopted and continuous cultivation discouraged to increase water infiltration on sloppy terrains of the study area.